Assessment of Functional and Biochemical Parameters in Healthy Young Men with Different Somatotypes - Anton Yu. Prikhodko; Mikhail S. Golovin; Vladimir M. Klimov; Sergey G. Krivoshchekov; Roman I. Aizman (Northern (Arctic) Federal University, 2024)
The purpose of this article was to study the functional and biochemical characteristics of the body before and after an exercise test as well as physical performance and muscular endurance in young men with different somatotypes. Materials and methods. The research involved 29 apparently healthy young men aged 18 to 22 years, who performed an exercise step test to failure on a treadmill. We assessed the subjects' somatotype (according to the Heath-Carter method), anthropometric parameters, hand muscle strength and endurance, type of functional response, blood pressure, heart rate, as well as capillary blood glucose and lactate levels. All of the above were measured at the beginning of the test, during the transition between the steps (a 10-15-second pause) and immediately after the subjects' failure to continue the test. Results. We found that ectomorphs differed from the subjects with other somatotypes, especially endomorphs, by having a higher level of functional capabilities and greater contribution of aerobic processes to the body's energy supply, as well as smaller homeostatic shifts in the cardiovascular system and lower blood glucose and lactate concentrations after maximum physical exertion. Compared to their peers with other somatotypes, endomorphs showed a higher contribution of the lactate mechanism to the energy supply and lower functional capabilities, which were manifested in more pronounced functional and biochemical shifts after physical exertion. Mesomorphs occupied an intermediate position between endo- and ectomorphs in terms of many morphofunctional and biochemical parameters. Аt the same time, mesomorphs' hand muscle endurance was the lowest, while their hand strength was the greatest.